Vitamin D Levels and Insulin Resistance in Children Born with Severe Growth Restriction - Giapros, V. I.; Challa, A. S.; Cholevas, V. L.; Evagelidou, E. N.; Bairaktari, E. T.; Andronikou, S. K. (Hormone and Metabolic Research, 2013)
This study was designed to examine differences in serum 25(OH)D levels between small-for-gestational-age (SGA) and appropriate-for-gestational-age (AGA) prepubertal children in correlation with birth weight and indices of insulin resistance and β-cell function. Sixty-five nonobese children were examined at age 5–7.5 years; 27 born SGA and 38 matched AGA. Body weight, height, BMI, and waist circumference were recorded and fasting serum levels of glucose, insulin, 25(OH)D, and parathyroid hormone (PTH) were measured. The homeostasis model assessment for insulin resistance (HOMA-IR) and the β-cell function index (HOMA-β%) were estimated. The mean level of 25(OH)D was higher in the SGA group (26.2±10 vs. 17.2±7 ng/ml, p<0.01) but that of PTH was no different. The insulin resistance and β-cell function indices were higher in the SGA group: HOMA-IR 1.34±0.67 vs. 0.99±0.53, and HOMA-β% 135±56 vs. 97±60 in the SGA and AGA groups, respectively. In the SGA group, 25(OH)D was correlated with HOMA-β% but not with HOMA-IR or insulin. In multiple regression, in the total cohort 25(OH)D and HOMA-IR were independently negatively correlated with birth weight (β= − 0.31, β= − 0.36, p<0.05) respectively. In conclusion, at prepuberty severely in utero growth restricted children have increased birth weight dependent levels of 25(OH)D, which might exert a regulatory role on β-cell function.
Keywords: vitamin D; small-for-gestational-age; insulin resistance; β-cell function; in utero growth restriction